SISTEM INFORMASI TUNJANGAN PENDAPATAN KEPEGAWAI DI KANTOR KECAMATAN MENGGUNAKAN FRAMEWORK CODEIGNITER - Selviani, Rima; Haq, Haris Nizhomul; Sobari, Dicky Iskandar (STMIK Subang, 2024)
In the current era of technological advancements, the demand for information has significantly risen across various facets of life. The Employee Income Allowance Information System (TPP) implemented at the Subang Sub-District Office encompasses comprehensive data, including employee profiles, attendance records, TPP reports, and employee assessments. This system facilitates employees in efficiently accessing and reviewing attendance and TPP report data. The implementation is carried out using CodeIgniter, PHP, and MySQL technologies.